1992
DOI: 10.2169/internalmedicine.31.1381
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Case of Severe Chronic Active Epstein-Barr Virus Infection Syndrome.

Abstract: A 23-year-old man with persisting high fever developed hepatosplenomegaly, lymphadeno pathy and massive pericardial effusion. Immunologieal examination revealed a marked elevation of anti-Epstein-Barr virus antibodies (anti-viral capsid antigens IgG-antibody 1:10,240, anti early antigens-DR IgG-antibody 1:5,120), decreased activities of Epstein-Barr virus specific cytotoxic T lymphocytes, natural killer cells and lymphokine activated killer cells. A liver biopsy showed moderate sinusoidal lymphocytosis with pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…No immune deficiency was detected, but virus-specific, cytotoxic T lymphocyte studies have not been done. NK cell number and function were normal in our patient, unlike in many other reported cases [32][33][34], which also is in keeping with the relatively low number ofEBV-containing mononuclear cells detected in the patient's peripheral blood.…”
Section: Discussionsupporting
confidence: 85%
“…No immune deficiency was detected, but virus-specific, cytotoxic T lymphocyte studies have not been done. NK cell number and function were normal in our patient, unlike in many other reported cases [32][33][34], which also is in keeping with the relatively low number ofEBV-containing mononuclear cells detected in the patient's peripheral blood.…”
Section: Discussionsupporting
confidence: 85%
“… 12 , 13 However, similar clinical conditions have also been reported in adults (EBV-T/NK-LPD with CAEBV-like features in adult; adult-onset CAEBV). 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hepatic sinusoidal lymphocytosis also occurs in chronic infections with EpsteinBarr and hepatitis C viruses, and Felty's syndrome and is therefore a non-specific finding. [27][28][29] Despite these diagnostic difficulties it is crucial to make the correct diagnosis as HMS responds well to malaria prophylaxis whereas SLVL, particularly if symptomatic, may require splenectomy. 30 The criteria for HMS were established before SLVL was described and because of the reasons outlined we have found that they are not sufficiently stringent to distinguish between these two conditions.…”
Section: Tropical 'Big Spleen' Disease -The Role Of Malariamentioning
confidence: 99%